Incidence, diagnosis, and management of injury in sport climbing and bouldering: A critical review - Jones, G.; Schöffl, V.; Johnson, M. I. (Current Sports Medicine Reports, 2018)
Competition climbing will debut as an Olympic sport at the 2020 summer games in Tokyo. The aim of this article is to critically review research on the incidence of injury in sport climbing and bouldering. The pathophysiology and clinical presentation of finger and shoulder injuries is discussed. A semisystematic approach in reviewing literature on incidence was applied. Articles were identified after searches of the following electronic databases: Discover, Academic Search Complete (EBSCO), PubMed, Embase, SPORTDiscus, and ScienceDirect. Despite methodological shortcomings of the included studies, we estimated the mean ± SD of the incidence rate of injury in sport climbing and bouldering from the eight studies to be 2.71 ± 4.49/1000 h. Differential diagnosis and the clinical management of finger and shoulder injuries in climbers are challenging. An updated diagnostic and therapeutic algorithm for the clinical management of finger injuries in climbers is presented.